A Rare Case of Herlyn Werner Wunderlich Syndrome (HWWS) with Urethrovaginal Fistula - Meher-un-Nisa, Maria Maqsood, Aleena Sarwar, Tayyaba Iqbal, Ayesha Siddiqa, Ayesha Sabrina Aslam (Pakistan Journal of Medical & Health Sciences, 2022)
Herlyn Werner Wunderlich Syndrome (HWW) is a rare congenital malformation of female urogenital tracts. We report our first case of HWWS with urethrovaginal fistula in Lady Aitchison Hospital Lahore. A 27 years old lady presented with hematuria and urinary retention having single opening at vulva with menstrual blood and urine draining through it. Examination under anesthesia showed uretheral opening in anterior wall of lower 1/3 of vagina.MRI showed uterus didelphus with two cervices and vagina (atresia of lower 2/3 on left side) and absent left kidney.Surginal treatment by creating a separate opening of neourethra was made by Urology Department of Mayo Hospital. Keywords: Herlyn Werner Wunderlich syndrome, urethrovaginal fistula, urogenital tract